Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To determine which equation can replace [tex]\( 3x + 5y = 59 \)[/tex] in the original system while still producing the same solution, we will use the method of linear combination (also known as the elimination method).
The original system of equations is:
1) [tex]\( 3x + 5y = 59 \)[/tex]
2) [tex]\( 2x - y = -4 \)[/tex]
We aim to find another equation that can replace the first equation [tex]\( 3x + 5y = 59 \)[/tex] and still result in the same solution for [tex]\( x \)[/tex] and [tex]\( y \)[/tex].
Let's manipulate the second equation to see if we can form an equivalent equation.
Given:
[tex]\[ 2x - y = -4 \][/tex]
Multiply the entire equation by 5:
[tex]\[ 5 \cdot (2x - y) = 5 \cdot (-4) \][/tex]
This yields:
[tex]\[ 10x - 5y = -20 \][/tex]
Now we have:
[tex]\[ 10x - 5y = -20 \][/tex]
We need to check whether substituting [tex]\( 10x - 5y = -20 \)[/tex] in place of [tex]\( 3x + 5y = 59 \)[/tex] allows the system to retain the same solution for [tex]\( x \)[/tex] and [tex]\( y \)[/tex].
To summarize, the equation that can replace [tex]\( 3x + 5y = 59 \)[/tex] while still producing the same solution is:
[tex]\[ 10x - 5y = -20 \][/tex]
Thus, the correct equation is:
[tex]\[ \boxed{10x - 5y = -20} \][/tex]
The original system of equations is:
1) [tex]\( 3x + 5y = 59 \)[/tex]
2) [tex]\( 2x - y = -4 \)[/tex]
We aim to find another equation that can replace the first equation [tex]\( 3x + 5y = 59 \)[/tex] and still result in the same solution for [tex]\( x \)[/tex] and [tex]\( y \)[/tex].
Let's manipulate the second equation to see if we can form an equivalent equation.
Given:
[tex]\[ 2x - y = -4 \][/tex]
Multiply the entire equation by 5:
[tex]\[ 5 \cdot (2x - y) = 5 \cdot (-4) \][/tex]
This yields:
[tex]\[ 10x - 5y = -20 \][/tex]
Now we have:
[tex]\[ 10x - 5y = -20 \][/tex]
We need to check whether substituting [tex]\( 10x - 5y = -20 \)[/tex] in place of [tex]\( 3x + 5y = 59 \)[/tex] allows the system to retain the same solution for [tex]\( x \)[/tex] and [tex]\( y \)[/tex].
To summarize, the equation that can replace [tex]\( 3x + 5y = 59 \)[/tex] while still producing the same solution is:
[tex]\[ 10x - 5y = -20 \][/tex]
Thus, the correct equation is:
[tex]\[ \boxed{10x - 5y = -20} \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.